THE INFLUENCE OF THE RESPONSIBILITY OF AQIDAH AKHLAK TEACHERS ON THE LEARNING DISCIPLINE OF CLASS VIII STUDENTS AT MTS GUPPI TAIPALE'LENG, GOWA REGENCY (International Conference on Social and Islamic Studies, 2022)
This study discusses "The Influence of the Responsibility of Aqidah Akhlak Teachers on the Learning Discipline of Class VIII Students at MTs Guppi Taipale'leng, Gowa Regency" which aims to; 1) Knowing the responsibilities of the moral creed teacher at MTs Guppi Taipale'leng, Gowa Regency; 2) Knowing the learning discipline of class VIII students at MTs Guppi Taipale'leng, Gowa Regency; 3) Knowing the influence of the responsibilities of the teacher of aqidah morals on the learning discipline of class VIII students at MTs Guppi Taipale'leng, Gowa Regency. The type of research used in this study is a type of quantitative research that is ex-post facto which means after the incident. This research was conducted at MTs Guppi Taipale'leng, Gowa Regency. The population in this study were 40 grade VIII students at MTs Guppi Taipale'leng, Gowa Regency. While the sample in this study were 40 people using a sampling technique, namely saturated sampling technique. Collecting data in this study used a questionnaire with a scale of teacher responsibility and a scale of learning discipline which were analyzed using descriptive statistics and inferential statistics. Based on the results of the descriptive statistical analysis, it was found that the results of the research on the responsibilities of the teacher's aqidah morals were in the low category as much as 5%, as much as 90% in the medium category, and as much as 5% in the high category. So it can be concluded that the responsibility of the teacher of aqidah morals at MTs Guppi Taipale'leng Gowa Regency is in the medium category with a percentage of 90%. Meanwhile, the results of the study discipline research for class VIII students were in the low category of 0%, the medium category was 95%, and the high category was 5%. So it can be concluded that the learning discipline of class VIII students at MTs Guppi Taipale'leng Gowa Regency is also in the medium category with a percentage of 95%. From the calculation results obtained (tcount) = 6.71 while (ttable) = 1.662 for a significance level of 0.05%. Because tcount is greater than ttable, it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of the responsibilities of the aqidah moral teacher on the learning discipline of class VIII students at MTs Guppi Taipale'leng, Gowa Regency. The implication of this research is for teachers, especially teachers of aqeedah moral subjects, to pay more attention to students related to what is being taught to foster or create the character of students to be more disciplined in terms of learning, for students to pay more attention and remember that learning discipline is within the scope of schooling greatly influences him, for the principal to pay more attention to what causes the participants to be undisciplined in terms of learning and for future researchers, it can be used as reference material in conducting research on the responsibilities of teachers' moral beliefs and student learning discipline.